2019
DOI: 10.1155/2019/5030349
|View full text |Cite
|
Sign up to set email alerts
|

Serum Tumour Markers in Testicular Germ Cell Tumours: Frequencies of Elevated Levels and Extents of Marker Elevation Are Significantly Associated with Clinical Parameters and with Response to Treatment

Abstract: Introduction. Although serum tumor markers beta human chorionic gonadotropin (bHCG), alpha-fetoprotein (AFP), and lactate dehydrogenase (LDH) are well-established tools for the management of testicular germ cell tumours (GCTs), there are only few data from contemporary cohorts of primary GCT patients regarding these biomarkers. Our aim was to evaluate marker elevations in testicular GCTs and to document their associations with various clinical characteristics.Patients and Methods. A total of 422 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 76 publications
6
73
0
2
Order By: Relevance
“…The most important diagnostic gain of using miRNAs is in patients with seminomas, since β-HCG is only elevated in a subset of these patients and LDH is not a reliable tumor marker (30-50% [7,10]). Accordingly, in our study, the STMs showed a sensitivity of 31% for diagnosing primary seminomas, whereas the miRNAs (miR-371a-3p and/or miR-372-3p and/or miR-373-3p) had a sensitivity of 71%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important diagnostic gain of using miRNAs is in patients with seminomas, since β-HCG is only elevated in a subset of these patients and LDH is not a reliable tumor marker (30-50% [7,10]). Accordingly, in our study, the STMs showed a sensitivity of 31% for diagnosing primary seminomas, whereas the miRNAs (miR-371a-3p and/or miR-372-3p and/or miR-373-3p) had a sensitivity of 71%.…”
Section: Discussionmentioning
confidence: 99%
“…To establish whether measuring miRNAs adds value beyond the primary diagnosis, large prospective clinical trials comparing miRNAs and classical tumor markers during the treatment and follow-up of TGCT patients are needed.Cancers 2020, 12, 759 2 of 16 HCG; 7 days for AFP). A major problem is, however, that the STMs are only elevated in 48-60% of TGCT cases at primary diagnosis, irrespective of histological type [4][5][6][7].As an alternative, or in addition to, the STMs, a panel of circulating microRNAs (miR-367-3p, miR-371a-3p, miR-372-3p, and miR-373-3p) has been investigated intensively, due to their high expression in most TGCTs (except teratomas). These miRNAs have been proposed as novel biomarkers that could replace the STMs in the clinical management of patients with TGCTs (for reviews, see Almstrup et al [8], Lobo et al [9] and Murray et al [6]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of microRNAs (miRs) of the clusters miR-371-373 and miR-302/367 have been suggested as novel biomarkers of testicular germ cell tumors (GCTs) [1][2][3]. Of the candidate miRs, miR-371a-3p appears to be the most promising serum marker of GCT with a sensitivity of 90.1% and specificity of 94.1% [4,5] outperforming the classical markers (alpha fetoprotein, beta human chorionic gonadotropin, lactate dehydrogenase) with their sensitivities of less than 50% [6]. Apparently, miR-371a-3p features almost all of the qualities a valuable tumor marker is supposed to have [7] since it correlates with clinical stages, and tumor sizes, it highlights response (or non-response) to therapy, and it is present in cases with relapsing GCT suggesting a prominent role of this miR upon follow-up examinations [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation of these biomarkers is that they are differently expressed in the various histological subgroups of GCTs. In seminoma, the most frequent subgroup, bHCG and LDH are expressed in roughly 30% of cases, while AFP is not (2). In nonseminoma, the other main subgroup, all three markers are expressed in 30-60% of cases (3,4).…”
mentioning
confidence: 98%